A Late devonian reef tract on northeastern Banks Island, N.W.T. ... - Embry, Ashton F. Ashton Fox (University of Calgary, 1970)
Bibliography: p. 116-118. ... : The exposed Upper Devonian succession on northeastern Banks Island, N.W.T. is 3700 feet thick and has been correlated with the Griper Bay Formation. It consists mainly of terrigenous elastic rocks which were deposited in a marine shelf to coastal complex environment. The source area was located to the west. The age of the exposed section ranges from the base of the Frasnian to the Middle Famennian. Devonian strata have been moderately deformed,and north-south trending folds and normal faults are present. Deformation occurred during the Mississippian,and the structures were reactivated in the Tertiary. A 200 foot carbonate unit occurs in the middle of the succession . It has been herein named the Mercy Bay Member and is of Middle Frasnian age. It contains many organic buildups and represents a Devonian reef tract. The reef tract was located on the western shelf of an exogeosyncline which extended along the margin of North America between the stable craton and a western tectonic highland. The main facies ...